2016
DOI: 10.1292/jvms.15-0594
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and susceptibilities to disinfectants of <i>Cryptococcus neoformans</i> in fecal droppings from pigeons in Bangkok, Thailand

Abstract: Cryptococcus neoformans is an opportunistic pathogenic yeast that causes meningoencephalitis and deep skin dermatitis in humans and animals. A hygienic strategy using disinfectants on environmental samples can reduce the risk to the public. The objectives were to survey the distribution of C. neoformans in pigeon fecal droppings collected in 11 districts in Bangkok during 2011–2012 and to evaluate the efficacy of three commercial disinfectant products (based on potassium monopersulfate, sodium hypochlorite and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Contaminated soils near a hospital have been suggested as sites for hospital-acquired infection of C. neoformans (49). Remediation of C. neoformans -contaminated soils is a formidable challenge and current methods involve the application the noxious chemicals such as formalin (50) and quaternary ammonium salts (51). Given that amoeba predation can reduce fungal burden in contaminated soils (29), our results suggest that increasing the soil concentration of divalent cations with calcium and magnesium salts could potentiate the fungicidal capacity of amoeba and provide a more environmentally friendly biological alternative to chemical decontamination.…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated soils near a hospital have been suggested as sites for hospital-acquired infection of C. neoformans (49). Remediation of C. neoformans -contaminated soils is a formidable challenge and current methods involve the application the noxious chemicals such as formalin (50) and quaternary ammonium salts (51). Given that amoeba predation can reduce fungal burden in contaminated soils (29), our results suggest that increasing the soil concentration of divalent cations with calcium and magnesium salts could potentiate the fungicidal capacity of amoeba and provide a more environmentally friendly biological alternative to chemical decontamination.…”
Section: Discussionmentioning
confidence: 99%
“…Las frecuencias de muestras positivas en heces de palomas en otros países varían desde 1.4% hasta valores tan altos como 34% (Curo, 2005;Cermeño et al, 2006;Zarrini et al, 2010;Soltani et al, 2013;Huamán et al, 2018), así como en heces de canarios y gallinas (Criseo et al, 1995;Kuroki et al, 2004;Cafarchia et al, 2006). Esto evidencia su importancia como patógeno y el riesgo que representa para la salud pública (Kuroki et al, 2004 La ausencia de C. neoformans en las muestras de heces de las palomas mensajeras criadas en cautiverio en los cuatro palomares del estudio se debería posiblemente al manejo de los ambientes de crianza y a las actividades periódicas de desinfección que se realizan calendarizados, limpieza de excretas del suelo y de los nidales (Krangvichain et al, 2016;Huamán et al, 2018).…”
Section: Discussionunclassified
“…A prior study found that quaternary ammonium compounds effectively killed all C. neoformans yeasts in pigeon droppings within 30 min of contact time at a concentration of 0.062%, while rapid killing was observed at a concentration of 0.5% (44). At the facilities in this study, a concentration of 0.4% was typically used, with a 30-min contact period.…”
Section: Discussionmentioning
confidence: 99%